A Proposed Framework for Analyzing Performance of Routing Protocols in Wireless Sensor Network Using a Network Simulator - Mustafa, Hashmi (2004)
Dramatic advancements in micro-electro-mechanical and wireless communication technology have heightened the usage of sensor networks. Much interest has been seen towards Sensor Network (SN) routing protocol research; however, lack of research tools preventing more people to endeavor into the routing protocol research. This thesis is an infinitesimal effort to fill this research gap by proposing a framework to analyze the performance of the SN routing protocols. Using content analysis approach to quantitative research and all-embracing study of power aware routing protocols. Using content analysis approach to quantitative research and all-embracing study of aware routing protocols especially LEACH, SPIN and PEGASIS, several simulation requirement models from both hardware and software perspectives have been studied. These simplified models are further classified into several submodels and simulaton classes which can be implemented on widely acclaimed discrete even-driven simulation environment, the ns-2. We believe that our proposed framework for sensor networks routing protocols' appraisal-oriented studies, by all means provides a preordained research platform to novice researchers to start-off-their research.